THE PERSPECTIVES OF BUDGET FEDERALISM’S INTRODUCTION IN UKRAINE - Treschov M.М. (Pressing Problems of Public Administration, 2015)
Approaches to the interpretation of the concept of “fiscal federalism” are researched. Its general principles and features are determined. The prospects of implementing specific aspects of fiscal federalism in the process of transformation of the budget and tax systems Ukraine are proposed.